2009
DOI: 10.1007/s00774-009-0074-6
|View full text |Cite
|
Sign up to set email alerts
|

Total body, lumbar spine and hip bone mineral density in overweight adolescent girls: decreased or increased?

Abstract: Despite the epidemic of overweight adolescents, the effect of being overweight on bone mineral density (BMD) during this period is poorly understood. However, recent studies have suggested that overweight adolescents have lower BMD compared to normal-weighted adolescents after adjusting for body weight. The aim of this study was to determine the influence of being overweight on bone status in a group of adolescent girls. This study included 22 overweight (BMI >25 kg/m(2)) adolescent girls (15.4 +/- 2.4 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 17 publications
2
21
0
2
Order By: Relevance
“…Body composition (lean mass, fat mass, and fat mass percentage) was measured by DXA (Hologic QDR-4,500W). In our laboratory, the in vivo coefficients of variation were 1.13 and .54% for fat and lean mass, respectively [12,13].…”
Section: Anthropometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Body composition (lean mass, fat mass, and fat mass percentage) was measured by DXA (Hologic QDR-4,500W). In our laboratory, the in vivo coefficients of variation were 1.13 and .54% for fat and lean mass, respectively [12,13].…”
Section: Anthropometrymentioning
confidence: 99%
“…The DXA measurements were completed for the whole body (WB) using the instrument described earlier. The Hologic APEX software, version 2 (1986-2007, Hologic Inc.) was used to analyze the DXA scans on the Hologic machine.The coefficients of variation were <1% for BMC and BMD in our laboratory [12,13]. Bone mineral apparent density (BMAD g/cm 3 ), an estimate of volumetric bone density, was calculated as described previously [14].…”
Section: Bone Measurementsmentioning
confidence: 99%
“…In fact, obesity and overweight are associated with higher BMD and decreased risk of fracture especially in post-menopausal women [2]. However, the effects of being obese and overweight on bone strength in adolescents remain controversial [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. There are different methods used to analyze bone strength.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study support the conclusions of prior studies (Cobayashi, et al, 2005;El Hage, Jacob, Moussa, Benhamou, & Jaffre, 2009;Ellis, et al, 2003;Leonard, et al, 2004;Sayers & Tobias, 2010), which reported greater body weight or BMI was associated with higher whole body or region specific BMC/ bone mass or bone density.…”
Section: Discussionsupporting
confidence: 82%